Upaya Guru PAI dalam Membentuk Karakter Islami Peserta Didik Kelas XI di SMK PP Negeri Padang - Putri, Ananda Maharani; Ikhlas, Al (TSAQOFAH, 2025)
The phenomenon of moral crisis among vocational high school (SMK) students reflected in undisciplined behavior, lack of respect for teachers, and low religious awareness forms the critical background of this study. The research aims to analyze the efforts of Islamic Religious Education (PAI) teachers in shaping the Islamic character of Grade XI students at SMK Pertanian Pembangunan Negeri Padang. A qualitative approach with a case study method was employed, and data were collected through in-depth interviews, observation, and documentation involving PAI teachers, the vice principal, and students. The findings reveal that PAI teachers apply various strategies, including habituation of obligatory worship, role modeling in attitude and behavior, integration of character values into learning processes, and student involvement in school-based religious activities. Supporting factors for these efforts include school policy support, a religious school environment, and parental involvement. Challenges include negative external influences, low motivation among some students, and limited time for character development. The study concludes that the role of PAI teachers is highly strategic in shaping students’ Islamic character through a holistic approach that combines example, habituation, and motivation. The study recommends strengthening character education programs based on Islamic values as an integral part of the educational system in vocational schools.